Ocorrência de Escherichia coli produtora de toxina Shiga (STEC) no processamento da carne bovina - Santos, Elis Caroline Celestina dos (2016)
The Brazil is responsible for about 15% of world production of beef, the largest exporter of this product, serving more than 100 countries. To maintain competitiveness, investments are needed in quality programs as Good Manufacturing Practices and Hazard Analysis and Critical Control Points. Enterobactéria, coliforms and Escherichia coli are important hygiene indicators in the processes of obtaining the beef. Processed meat products marketed chilled or frozen, use in its formulation meat of the front (masseter, esophagus, diaphragm and boning flaps), which can be contaminated during procedures skinning and gutting, being with a mind biohazard, especially for the presence of pathogenic strains of Escherichia coli, such as producing Shiga toxin. Nine are known pathogenic serotypes of E. coli, however, for public health E. coli producing shiga toxin (STEC) is one of the most relevant pathotypes at the expense of its relationship to some diseases caused by the production of this toxin in food. Objective with this study was to verify the occurrence of Escherichia coli producing Shiga toxin (STEC) in the processing of beef. The environmental conditions were evaluated using swabs of bleeding knives, skinning, boning and boning tables, for a total of 52 samples submitted to entrebatérias count, E. coli and total coliforms, all the Petrifilm® method (3M). A total of 10 carcasses were followed in this study, and the samples taken from eight different points of slaughter flowchart, totaling 80 samples that were subjected to Polymerase Chain Reaction (PCR) duplex for research STEC. The knives bleeding and skinning stage showed the presence of E. coli in 61.5% of samples, between meat cuts 30.76% of the samples of masseter, esophagus and boning patchwork showed the presence of E. coli up to count 2 log CFU/g and 15.3% of diaphragm samples up to 1.85 log CFU/g. A total of 27.7% (37/134) of colonies of E. coli were genotyped as STEC. The highest frequency of STEC occurred in leather and rectum, however, it was also verified the presence in the masseter, diaphragm, esophagus, carcasses and bones flaps. The frequency of genotypes were Stx2 10.8% (4/37), Stx2 / ehx 59.4% (22/37), Stx1 / Stx2 / ehx / uid 5.5% (2/37), Stx1 / eae 2 7% (1/37), Stx2 / eae 8% (3/37), Stx2 / ehx / eae 2.7% (1/37), Stx1 / Stx2 / ehx 8% (3/37). With the data obtained, it can be said that the sanitation strategies and hygiene equipment and utensils used in the refrigerator, were not very efficient to eliminate Escherichia coli, and leather and fecal content are the main sources of STEC contamination, skinning and gutting steps spread the contamination to the masseter muscle, diaphragm, esophagus, carcasses and meat in natura cold cuts. The occurrence of STEC over meat processing indicates poor hygiene and brings negative consequences to public health and the export of beef.